Model Latihan Blocking Penjaga Gawang Berbasis Small Sided Games Pada Klub Sepak Bola Wanita di Jakarta - Safiyah, Sarah Dzikra; Fitranto, Nur; Sujiono, Bambang (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2024)
This research aims to develop a blocking training model based on small sided games in newer and simpler soccer games so that it is easy to understand and apply directly for goalkeepers of women's soccer clubs in Jakarta. The development of a goalkeeper blocking training model based on small sided games in this soccer game uses the Research and Development method which refers to the BORG GALL model. This research initially created a product design of 13 training models, then the final results using expert justification tests became 13 training models. Based on the validation test used is an expert justification test with three experts in the field of soccer. The purpose of this research is as reference material to improve skills, success and provide variations in goalkeeper blocking exercises during game situations. This training model also aims to be a reference for football coaches, especially women's football clubs in Jakarta, in implementing blocking exercises based on small sided games which can be carried out during training and matches. It is hoped that the results of this research in the future can become reference material for coaches and students who will develop this model and especially for female soccer goalkeepers in improving their blocking technique abilities in soccer games